The experience of traditional massage practitioners in supporting breastfeeding practice - Muda, Siti Mariam; Hasan, Haliza (International Journal of Children, Women, Elderly and Disable People, 2019)
ABSTRACT Strategies that have been successful in promoting breastfeeding practice and to increase breastfeeding education include mother-to-mother support and close contact with breastfeeding support members through home visits. The objective of this study is to explore the experience of traditional massage practitioners in promoting and supporting breastfeeding practice. A qualitative study using semi structured face-to-face interview was conducted among breastfeeding support group members who are working as traditional massage practitioners. The data was transcribed and analyzed using thematic analysis. Three themes were revealed involving participants real enjoyed the experiences, gaining knowledge on breastfeeding technique and breastfeeding challenges. This study identified that the traditional massage practitioners have shown good support towards breastfeeding practice and recommended the need of massage therapy for continuity of this practice.